Novel 3, 3-disubstituted oxindole derivatives. Synthesis and evaluation of the anti-proliferative activity. Issue 2 (15th January 2020) - Christodoulou, Michael S.; Nicoletti, Ferdinando; Mangano, Katia; Chiacchio, Maria Assunta; Facchetti, Giorgio; Rimoldi, Isabella; Beccalli, Egle M.; Giofrè, Sabrina
Graphical abstract: Abstract: 3, 3-Disubstituted oxindole derivatives bearing a nitrogen atom at the C-3 position have been synthesized starting from 3-alkyl oxindole through a metal free pathway. These derivatives have been tested in five human tumor cell lines (PC3, MCF7, SW620, MiaPaca2 and A375) and on primary cells (PBMCs) from healthy donors providing compound 6d showing a strong anticancer effect in all cancer lines on the low micromolar range.